Capital investments and financial profitability - Suzana Baresa; Sinisa Bogdan; Zoran Ivanovic (UTMS Journal of Economics, 2016)
Economic life of achieving economic and financial effects of an investment opportunity presents the period in which selected investment option remains economically superior from the other alternative investment opportunity. Time period in which the investment project needs to prove its justification, presents an extremely critical factor in the profitability of the investment project, therefore, special attention must be paid to the assessment of the economic and financial time period. The aim of this study was to prove that critical factor in achieving profitability is in direct relation with economic or financial life. The results which arise from this study suggest on the fact that during analysis investor must determine financial life to achieve economic and financial effects of capital investment, because the length of the economic life does not have to match the profitability or with financial efficiency, and that is not appreciated sufficiently in practice. This paper presents examples of calculating the financial profitability of capital investment, using the residual value, ie the discounted residual value and the results of empirical studies that show the difference in preference of life effectuation of capital investment between theoreticians and practitioners in the field of capital budgeting.
Keywords: G31; 330; net cash flow; discounting; economic life; financial life and residual value